Technical considerations to development of serological tests for SARS-CoV-2 - Ernst, Emilie (Talanta, 2021)
The COVID-19 pandemic has had a devastating impact worldwide and has brought clinical assays both for acute diagnosis and prior exposure determination to the forefront. Serological testing intended for point-of-care or laboratory use can be used to determine more accurate individual and population assessments of prior exposure to SARS-CoV-2; improve our understanding of the degree to which immunity is conveyed to subsequent exposures; and quantify immune response to future vaccines. In response to this pandemic, initially more than 90 companies deployed serology assays to the U.S. market, many of which made overstated claims for their accuracy, regulatory approval status, and utility for intended purpose. The U.S. Food and Drug Administration subsequently instituted an Emergency Use Authorization (EUA) procedure requiring that manufacturers submit validation data, but allowing newly developed serological tests to be marketed without the usual approval process during this crisis. Although this rapid deployment was intended to benefit public health, the incomplete understanding of immune response to the virus and lack of assay vetting resulted in quality issues with some of these tests, and thus many were withdrawn after submission. Common assay platforms include lateral flow assays which can serve an important niche of low cost, rapid turnaround, and increased accessibility whereas established laboratory-based platforms based on ELISAs and chemiluminescence expand existing technologies to SARS-CoV-2 and can provide throughput and quantification capabilities. While most of the currently EUA assays rely on these well-established platforms, despite their apparent technical simplicity, there are numerous practical challenges both for manufacturers in developing and for end-users in running and interpreting such assays. Within are discussed technical challenges to serology development for SARS-CoV-2, with an emphasis on lateral flow assay technology.